2016
DOI: 10.3389/fpls.2016.00937
|View full text |Cite
|
Sign up to set email alerts
|

Response and Tolerance Mechanism of Cotton Gossypium hirsutum L. to Elevated Temperature Stress: A Review

Abstract: Cotton is an important multipurpose crop which is highly sensitive to both biotic and abiotic stresses. Proper management of this cash crop requires systematic understanding of various environmental conditions that are vital to yield and quality. High temperature stress can severely affect the viability of pollens and anther indehiscence, which leads to significant yield losses. Cotton can respond to withstand adverse environmental condition in several phases among which the accumulation of chemicals is extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 96 publications
0
33
0
Order By: Relevance
“…Temperature stress may cause deleterious effects at cell and molecular level, their networking and also during protein synthesis [46,83]. Due to which a number of cellular abnormalities, metabolic imbalances, instable homeostasis and complex molecular reprogramming can be observed at transcriptional and post-transcriptional levels [62]. As we described earlier that heat stress is normally taken together with water deficit (drought) conditions normally in cotton plants thus fortifying the stress impact from both abiotic sources.…”
Section: Biochemistrymentioning
confidence: 95%
See 1 more Smart Citation
“…Temperature stress may cause deleterious effects at cell and molecular level, their networking and also during protein synthesis [46,83]. Due to which a number of cellular abnormalities, metabolic imbalances, instable homeostasis and complex molecular reprogramming can be observed at transcriptional and post-transcriptional levels [62]. As we described earlier that heat stress is normally taken together with water deficit (drought) conditions normally in cotton plants thus fortifying the stress impact from both abiotic sources.…”
Section: Biochemistrymentioning
confidence: 95%
“…High temperature stress is reported to affect the pollen viability and the anther indehiscence, resulting in lower seed setting rate and causing significant reductions in final yields [62]. It is extensively documented and believed that the most viable site to be attacked during the heat spells is the photosynthetic apparatus, which is the primary site for carbohydrate production and food supply to other plant parts.…”
Section: Physiologymentioning
confidence: 99%
“…In rice, several histone markers have been reported to be associated with transcriptional activation, such as di- and trimethylation of H3K4 (H3K4me2 and H3K4me3) and acylation of H3K9 and H3K27 (H3K9ac and H3K27ac). Among these, H3K4me3, a post translational modification (PTM) of histones 5 , 6 , is known to be a euchromatic marker that may facilitate transcription initiation and elongation events and increase transcriptional regulation of genes 7 , 8 . In plants, H3K4me3 histones are associated with transcription start sites (TSS) of expressed genes 9 and are usually located from ∌150 bp upstream of the TSS to ∌500 bp downstream in rice 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, high temperature has been reported as a serious threat to crop productivity (Zafar et al 2018). So, when cotton is exposed to high temperature for longer duration lead to wilting of leaf (Ahuja et al 2010;Zahid et al 2016), shedding of fruiting bodies, i.e., squares, buds, flowers and bolls (Cao et al 2008;Iqbal et al 2017), and decreased rate of photosynthesis is reported by Marchand et al (2005). Therefore, it is need of the time to focus on development of new germplasm which can cope with high temperature.…”
Section: Discussionmentioning
confidence: 99%